PENGGUNAAN ZAT WARNA ORGANIK UNTUK MENINGKATKAN PERFORMA PERALATAN SOLAR CELL MENGGUNAKAN METODA DENSITY FUNCTIONAL THEORY (DFT) - Imelda Imelda (Lantanida Journal, 2016)
To improve the performance of solar cell equipment can be used dye as a sensitizer, a sensitizer role is to help absorb visible light in equipment that uses a semiconductor with a wide band gap such as TiO2 and ZnO . The calculation methods used are computationally DFT and TD - DFT to determine the value of geometry optimization , energy , population density and optical properties . As for knowing the performance of experimental equipment can be obtained from the value of the open circuit voltage ( Voc ) , short circuit current density (Jsc), Fill Factor. The dye can be enhanced sensitivity capabilities with the engineering structure or conformation of the molecule.